Taxonomic composition and biodiversity of the gut microbiome from patients with irritable bowel syndrome, ulcerative colitis, and asthma - A. Y. Tikunov; A. N. Shvalov; V. V. Morozov; I. V. Babkin; G. V. Seledtsova; I. O. Voloshina; I. P. Ivanova; A. V. Bardasheva; V. V. Morozova; V. V. Vlasov; N. V. Tikunova (Вавиловский журнал генетики и селекции)
To date, the association of an imbalance of the intestinal microbiota with various human diseases, including both diseases of the gastrointestinal tract and disorders of the immune system, has been shown. However, despite the huge amount of accumulated data, many key questions still remain unanswered. Given limited data on the composition of the gut microbiota in patients with ulcerative colitis (UC) and irritable bowel syndrome (IBS) from different parts of Siberia, as well as the lack of data on the gut microbiota of patients with bronchial asthma (BA), the aim of the study was to assess the biodiversity of the gut microbiota of patients with IBS, UC and BA in comparison with those of healthy volunteers (HV). In this study, a comparative assessment of the biodiversity and taxonomic structure of gut microbiome was conducted based on the sequencing of 16S rRNA genes obtained from fecal samples of patients with IBS, UC, BA and volunteers. Sequences of the Firmicutes and Bacteroidetes types dominated in all samples studied. The third most common in all samples were sequences of the Proteobacteria type, which contains pathogenic and opportunistic bacteria. Sequences of the Actinobacteria type were, on average, the fourth most common. The results showed the presence of dysbiosis in the samples from patients compared to the sample from HVs. The ratio of Firmicutes/Bacteroidetes was lower in the IBS and UC samples than in HV and higher the BA samples. In the samples from patients with intestinal diseases (IBS and UC), an increase in the proportion of sequences of the Bacteroidetes type and a decrease in the proportion of sequences of the Clostridia class, as well as the Ruminococcaceae, but not Erysipelotrichaceae family, were found. The IBS, UC, and BA samples had signif icantly more Proteobacteria sequences, including Methylobacterium, Sphingomonas, Parasutterella, Halomonas, Vibrio, as well as Escherichia spp. and Shigella spp. In the gut microbiota of adults with BA, a decrease in the proportion of Roseburia, Lachnospira, Veillonella sequences was detected, but the share of Faecalibacterium and Lactobacillus sequences was the same as in healthy individuals. A signif icant increase in the proportion of Halomonas and Vibrio sequences in the gut microbiota in patients with BA has been described for the f irst time.